Bonding Through Contexts: Herstories Retold on YiXi Talks - Wan, Rong (International Journal of Linguistics, 2022)
No man is an island, which explains the necessity of zooming into the processes of social bonding and interactive alignment taking place between the speaker and the addressee. Therefore, this study incorporates the emerging notion of “bonding” (Ide and Hata 2020) into the extensively explored concept of “context”, in the hope of shedding light on social relationships that arise from public speakers and the audience in Chinese public speeches. Specifically, through the lens of the stories of marginal women stories narrated in YiXi Talks (the Chinese counterpart of TED), this study not only aims at the investigation of bonding effect achieved in public speeches. But more importantly, it attempts to bravely voice for women’s hardships and predicament, demonstrate their constant struggles and resistance against social inequalities and call for due attention and support to marginal women in China and beyond.